A new permeability model for argillaceous porous media under stress dependence with clay swelling. (1st March 2021) - Lei, Gang; Liao, Qinzhuo; Patil, Shirish; Zhao, Yang
Abstract: This paper derives a novel analytical model for stress dependent permeability of argillaceous porous media (APM) considering clay swelling using fractal theory. The model shows that the stress dependent permeability is a function of effective stress, clay content, clay expansion coefficient, initial irreducible water saturation and rock lithology. It is validated by the available test data from experimental studies and is shown to perform well. The presented model is then invoked to study the effects of relevant parameters on normalized permeability and irreducible water saturation. Under a given effective stress, the normalized permeability decreases with increasing clay content or increasing clay complete expansion coefficient. This work provides a comprehensive study on stress-dependent permeability in APM considering clay swelling, which is beneficial to analyzing the effect of clay content on permeability behavior of APM under stress dependence and clay swelling. In addition, the proposed model serves as a foundation for estimating physical parameters by inverse modeling.